Synthesis, spectroscopic and antibacterial studies of zinc(II) and copper(II) complexes containing amino acid thiourea ligands - Abdul Kadir Maisara, Ramli Rafidah, Ismail Noraznawati, (Universiti Pendidikan Sultan Idris, 2016)
Synthesis, spectroscopic and antibacterial studies of zinc(II) and copper(II) complexes containing amino acid thiourea ligands by Abdul Kadir Maisara, Ramli Rafidah, Ismail Noraznawati,